Risk factors and perinatal outcomes associated with idiopathic small for gestational age Taiwanese newborns. Issue 3 (22nd June 2013) - Hung, Tai‐Ho; Hsieh, T'sang‐T'ang; Lo, Liang‐Ming; Chiu, Tsung‐Hung; Hsieh, Ching‐Chang; Hsu, Jenn‐Jeih
Abstract: Objective: To determine risk factors and perinatal outcomes associated with small for gestational age (SGA) neonates among healthy pregnant women. Methods: A retrospective cohort study was conducted of 49 945 women who gave birth at Chang Gung Memorial Hospital, Taipei, Taiwan, after 24 weeks of pregnancy. Idiopathic SGA newborns (n = 3398) were characterized by a birth weight below the 10th percentile for mean weight corrected for GA and fetal sex. Results: Risk factors for idiopathic SGA newborns included hypercoiling of the umbilical cord (adjusted odds ratio [aOR], 3.3; 95% confidence interval [CI], 1.6–7.0); prior fetal death (aOR, 2.8; 95% CI, 2.0–3.9); primiparity (aOR, 1.5; 95% CI, 1.4–1.7); adolescent pregnancy (aOR, 1.5; 95% CI, 1.2–2.0), low prepregnancy weight (aOR, 1.6; 95% CI, 1.5–1.8), low prepregnancy body mass index (aOR, 1.1; 95% CI, 1.0–1.3); short stature (aOR, 1.3; 95% CI, 1.1–1.4); and entangled umbilical cord (aOR, 1.1; 95% CI, 1.0–1.3). Idiopathic SGA newborns correlated with increased risk of adverse perinatal outcomes, including fetal death, low Apgar scores, oligohydramnios, placental abruption, and admission to the neonatal intensive care unit. Conclusion: Some risk factors for idiopathic SGA newborns were modifiable, suggesting potential implications for public health.